The Relationship Between Psychological Factors And Posttraumatic Growth Among Head And Neck Cancer Patients - Abd Hamid, Norhaliza (2022)
Background: Head and neck cancer may lead to long term psychological complications, social and functional impairment among cancer survivors, which may affect the well-being and illness outcome. Nevertheless, collective evidence is accumulating regarding the positive impact of posttraumatic growth (PTG) on cancer survivors. PTG is a positive psychological change that develops in response to the traumatic or highly stressful experience of living with cancer. Despite its importance, data is still lacking on how various important psychosocial factors (hope, optimism, coping strategies and perceived spousal support) and psychological challenges (depression, anxiety and posttraumatic stress) were related to PTG among head and neck cancer patients across time. Hence, this study aimed to fill the research gap by evaluating the changes in hope and optimism, psychological challenges (depression, anxiety and posttraumatic stress), coping strategies, perceived spousal support [independent variables] and PTG [dependent variable] across time and their association among a cohort of head and neck cancer patients. Methods: The head and neck cancer participants were administered the sociodemographic and clinical characteristic questionnaires, the Malay versions of the Hope Scale, Life Orientation Test-Revised, Brief COPE, Sources of Social Support Scale, Hospital Anxiety and Depression Scale, PTSD Checklist for DSM-5 and Posttraumatic Growth Inventory-Short Form over two timepoints, such as baseline assessment and follow up assessment (between five and seven months after baseline assessments).